Sounding Islam : Voice, Media, and Sonic Atmospheres in an Indian Ocean World (2018)
Sounding Islam provides a provocative account of the sonic dimensions of religion, combining perspectives from the anthropology of media and sound studies, as well as drawing on neo-phenomenological approaches to atmospheres. Using long-term ethnographic research on devotional Islam in Mauritius, Patrick Eisenlohr explores how the voice, as a site of divine manifestation, becomes refracted in media practices that have become integral parts of religious traditions. At the core of Eisenlohr’s concern is the interplay of voice, media, affect, and listeners’ religious experiences. Sounding Islam sheds new light on a key dimension of religion, the sonic incitement of sensations that are often difficult to translate into language.